Beauty as a Criterion of Spiritual Discernment: an Outline of a Theory and Practice - Bernard Łukasz Sawicki (Polonia Sacra)
The goal of this paper is to indicate some possible ways of enriching the traditional approach to discernment by some new forms taken from fine arts. To achieve it, firstly different definitions of discernment are presented. Then, follows the presentation of some theological reasons for analogy between discernment and art. The next section develops the hypothesis resulting from the above analogy, in reference to some texts approaching discernment from the perspective of arts. The conclusion brings some practical indications.